VD_FINDINFO PP 36/08 - 16/2010 vom 18. März 2010 - VD Tribunal cantonal (2010)
PERTE DE GAIN, PRESTATION DE PRÉVOYANCE, PRÉVOYANCE PLUS ÉTENDUE | 34a LPP, 73 LPP, 24 al. 1 OPP2, 24 al. 2 OPP2, 106 LPA-VD, 117 al. 1 LPA-VD